Impactos macroeconômicos dos gastos públicos na América Latina - Alexandre Manoel Angelo da Silva; José Oswaldo Cândido Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper measures the public expenditure macroeconomic impacts (public consumption and public investment) in the more important Latin American economies by cointegrated autoregressive vectors. In the long run, public investments affect positively output and private consumption, although it has showed a substitution relationship with private investments. In the short run, government consumption multipliers used to be positive and statistically significant, although it has showed low impact. However, government investment multipliers used not to be statistically significant.
Keywords: H50; E62; C32; 330